Lichen sclerosus. - Tasker, G; Wojnarowska, F (2003)
Lichen sclerosus is a chronic skin condition, which offers many challenges to the clinician. It affects men, women and children, and usually occurs in the anogenital area. The clinical signs can be confused with those seen in sexual abuse in children. The underlying cause is unknown; however, there is a strong association with autoimmune disorders, and immunogenetic studies have demonstrated a link with HLA DQ7. Patients suffer significant morbidity as a consequence of the intractable symptoms, physical scarring and psychosexual damage. Support groups may be helpful for some patients. Potent topical corticosteroids have been shown to be effective. There is a 5% incidence of squamous cell carcinoma, and all suspicious lesions should be biopsied. It is unclear whether the risk of malignancy is changed with the use of topical corticosteroids, as there is a potential risk of triggering a latent infection of human papillomavirus. A multidisciplinary approach to care is required and ideally all patients should attend a dedicated clinic and be offered long-term monitoring.